Career aspirations of specialty among medical students in sub-Saharan Africa: a systematic review and meta-analysis of data from two decades, 2000–2021. Issue 8 (26th August 2022) - Bajunirwe, Francis; Semakula, Daniel; Izudi, Jonathan
Abstract : Objectives: To determine the distribution of career aspirations for the discipline of specialty among undergraduate medical students in sub-Saharan Africa (SSA). Design: We searched PubMed/MEDLINE, EMBASE Google Scholar and Google for studies published between 1 January 2000 and 31 June 2021. Two reviewers extracted data from eligible studies, with disagreements resolved through consensus with a third reviewer. The random effects model was used to pool proportions, presented with the corresponding 95% CI. Heterogeneity was assessed using Cochrane's (Q) test but quantified with I 2 values. Sources of heterogeneity were checked using meta-regression analysis while publication bias was assessed using funnel plot and Egger's test. Setting: SSA. Participants: Undergraduate medical students. Outcomes: Primary outcome was pooled proportion of career aspirations for the discipline of medical specialty and the secondary outcome was reasons for the specialty selection. Results: We identified 789 citations but meta-analysed 32 studies, with an overall sample size of 8231 participants. The most popular career aspiration for the discipline of specialty was surgery (29.5%; 95% CI 25.0% to 34.2%), followed by internal medicine (17.3%, 95% CI 11.7% to 23.7%), and then obstetrics and gynaecology (15.0%, 95% CI 12.3% to 17.9%), and paediatrics (11.3%; 95% CI 9.6% to 13.2%). The less popular medical disciplines of specialty included public health, orthopaedics, ophthalmology, family medicine, pathology, anaesthesiology, dermatology, otolaryngology, psychiatry and emergency medicine. The reasons for the selection of a medical discipline for specialty related to mentor and peer influences, prospect for economic gains, personal factors, long-term career interests and goals and discipline-specific factors. Conclusion: Surgery is the most preferred career aspiration for medical students in SSA, followed by internal medicine. The choices do not necessarily match the disease burden on the continent and medical schools should consider strengthening career counselling and mentoring in their curriculum. PROSPERO registration number: CRD42021260501.